Effects of Appetitive and Aversive Motivational States on Wanting and Liking of Interpersonal Touch. (1st June 2021) - Massaccesi, Claudia; Korb, Sebastian; Skoluda, Nadine; Nater, Urs M.; Silani, Giorgia
Highlights: Motivational states were induced to assess state-dependent effects on wanting and liking of interpersonal touch. Aversive motivation differentially affected social reward processing during anticipation and consumption phases. Being in an aversive state induced an enhancement of explicit wanting of interpersonal touch, but no changes in liking. Aversive motivation was associated with increased anticipatory pleasure during social reward anticipation. Abstract: Social rewards represent a strong driving force behind decisions and behaviors. Previous research suggests that the processing of a reward depends on the initial state of the individual. However, empirical research in humans on the influence of motivational states on reward processing is scant, especially for rewards of social nature. In the present study, we aimed at investigating how aversive and appetitive motivation affects the processing of social rewards, such as interpersonal touch. Participants ( n = 102) were assigned to an appetitive (positive) or aversive (negative) motivational state condition (via modified versions of the Trier Social Stress Test) or to a control condition. After the state induction, their (a) self-reports of wanting and liking, (b) effort, and (c) hedonic facial reactions during anticipation and consumption of interpersonal touch, were measured. Participants in the aversive group showed higher subjective wanting of interpersonal touch, but no changes in subjective liking, compared to the control group. The aversive group also showed stronger positive hedonic facial reactions during reward anticipation, reflecting stronger anticipatory pleasure. No significant effects were found for the appetitive group. The results indicate that, after being exposed to an aversive experience, the motivation to obtain interpersonal touch, as well as the associated anticipatory pleasure, increase, without a corresponding change in liking during or after its consumption. The findings point to differential state-dependent effects on the processing of social rewards, possibly due to the action of different neurobiological systems regulating reward anticipation and consumption.